How to invent and protect your invention : a guide to patents for scientists and engineers - Kennedy, Joseph Paul, 1928- (Wiley, 2012)
A straightforward guide to inventing, patenting, and technology commercialization for scientists and engineers Although chemists, physicists, biologists, polymer scientists, and engineers in industry are involved in potentially patentable work, they are often under-prepared for this all-important field. This book provides a clear, jargon-free, and comprehensive overview of the patenting process tailored specifically to the needs of scientists and engineers, including: Requirements for a patentable inventionHow to inventNew laws created by President Obama's.